Pengaruh Pembelajaran STEAM (Science, Technology, Engineering, Art and Mathematic) Terhadap Kreativitas Anak Usia 5-6 - Rosmalia; Djuko, Rapi Us; Rawanti, Sri (JURUSAN PENDIDIKAN GURU PENDIDIKAN ANAK USIA DINI, 2024)
This research aims to determine the Influence of STEAM (Science, Technology, Engineering, Art, and Mathematics) Learning Model on the Creativity of 5-6 Year-Old Children. This research is an experimental quantitative study (One group pretest-posttest design). The research population consisted of 15 children. The sample was 15 children aged 5-6 years old in Group B at TK Permata Sunnah Kindergarten, Kota Selatan District, Gorontalo City. Data analysis was conducted using statistical data processing. The research results indicated an increase in the average pre-test score, with an average score of 18.26 and a standard deviation of 3.71. Meanwhile, the post-test data obtained an average score of 31.8 and a standard deviation of 4.76. These results demonstrated a significant increase before and after the treatment. Based on the t-test results at (α) = 0.05, the t-table value was obtained as 2.131, then the t-count was calculated as 8.67. Thus, t-count > t-table; 8.67 > 2.131, meaning that since the tcount > ttable, the H0 was rejected, and the alternative hypothesis (H1) was accepted. Accepting the alternative hypothesis implies that there is an Influence of the STEAM Learning (Science, Technology, Engineering, Art, and Mathematics) on the Creativity of 5-6 Year-Old Children at TK Permata Sunnah Kindergarten, Kota Selatan District, Gorontalo City.